Exoneration Clauses in Information Technology-Based (Online) Money Loan Contracts - Wulandari, Fitria Devi; HS, Salim; Munandar, Aris (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This research aims to examine the characteristics of standard clauses containing exoneration clauses in information technology-based loan contracts (fintech lending) and analyze their legal consequences for consumer protection. The research method used is normative with a statutory approach, conceptual approach, and case approach. Online lending services are growing rapidly in the financial technology ecosystem, but the practice of drafting standard contracts often does not involve a negotiation process, resulting in an imbalanced position between service providers and users. The exoneration clause in the contract tends to absolve the provider from responsibility for user losses, which in principle contradicts the principles of justice and legal protection. The results show that exoneration clauses in standard fintech lending contracts have the potential to harm consumers and violate the provisions of the Consumer Protection Law. Therefore, it is necessary to strengthen regulations, more effective supervision, and increase legal literacy among the public so that consumers better understand the risks and their rights in digital transactions.